Advancement of Efﬁciency Evaluation for Healthcare : book chapter - Honcharuk, Anatolii H.; Гончарук, Анатолій Григорович; Canolle, Fabien; Antonic, Darijana; Melo, Paulo; Raposo, Vítor; Vinot, Didier (Springer, 2022)
The objective of this chapter is to provide conceptual understandings of evaluation methods for healthcare and concrete illustrations in order to take stock of the advancements and applications on the subject. The chapter is divided in four sections: the ﬁrst one sets the stage at a European level by evaluating healthcare system performance; the second goes back to the fundamental principles of methods of evaluation for healthcare; the third one follows with illustrations of patient-centred and person-centred methods of evaluation; and the last part moves forward with a reﬂection on intangibles and a proposition for a method of observation.
Advancement of Efﬁciency Evaluation for Healthcare / F. Canolle, D. Antonic, A. Casa Nova, A. Goncharuk, P. Melo, V. Raposo, D. Vinot // Intelligent Systems for Sustainable Person-Centered Healthcare. Intelligent Systems Reference Library. - Springer. - 2022, vol. 205. - P. 91-118.
Keywords: Efﬁciency evaluation; Methods; Person-centered; Value; Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::MEDICINE